The new watch - e uthor (London : William Heinemann, 2013)
Walking the streets of our cities are the Others. These men and women are guardians of the Twilight, a shadowy parallel world that exists alongside our own. Each has sworn allegiance to one side, fighting for the Light, or the Darkness. But now, beyond the continuing struggle comes a peril that threatens their very world...At Moscow airport, Higher Light Magician Anton Gorodetsky overhears a child screaming that a plane is about to crash. He discovers that the child is a prophet: an Other with the gift of foretelling the future. When the catastrophe is averted, Gorodetsky senses a disruption in the natural order, one that is confirmed by the arrival of a dark and terrifying predator. From the Night Watch headquarters Gorodetsky travels to London, to Taiwan and across Russia in search of clues, unearthing as he goes a series of increasingly cataclysmic prophecies. He soon realises that what is at stake is the existence of the Twilight itself - and that only he will be able to save it.
Translated from the Russian.
Keywords: Science fiction, Russian; Vampires -- Fiction